Analysis of beta carotene (carotenoid) in dark green vegetables using solid phase extraction (SPE) and high performance liquid chromatography- diode array detector (HPLC-DAD) / Fathin Nurshafiqa Mohd Zamri - Mohd Zamri, Fathin Nurshafiqa (2016)
A method for the quantification of beta carotene (carotenoid) in different dark green vegetables by using the solid phase extraction (SPE) and high performance liquid chromatography - diode any detector (HPLG-DAD) was developed. This analysis was done on the dark green vegetable species namely Spinaciaoleracea (Amaranthacea Group) 'spinach', Brassica oleracea (Italica Group) 'broccoli' and Brassica rapa spp. Chinensis (Brassicaceae Group) 'pak choi'. Firstly, each sample was homogenized with acetone and the extract was filtered before the cleaning up process using SPE. The CI8 SPE cartridge with bonded silica as the sorbent was used and it was conditioned with methanol prior to use. Polar solvent, 10% aqueous ethanol was used to remove the interferences in the sample matrix followed by nonpolar solvent, dichloromethane for the elution of beta carotene (analyte) from the cartridge. The analysis of beta carotene was done using HPLC-DAD equipped with RP-C18column with the injection volume of 20 uL, flow rate of 2.0 mL/min and visible detection at wavelength of 452 nm. Pak choi had the highest amount of beta carotene171.39 ± 20.45 mg/kg followed by spinach 146.34 ± 25.08 mg/kg and lastly broccoli22.38 ± 0.70 mg/kg.